(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
djadidy, Jadidism movement arose in the views of the advanced intellectuals of his time regarding backwardness and ignorance, the miserable condition of the country’s population, Turkestan’s lagging behind European and world civilization, the trampling of Islam and Sharia, and to get rid of such a difficult life, freedom and freedom. Awakening from the sleep of ignorance had become a historical necessity. In other words, the Jadidism movement was a huge social-political movement that appeared as a response to the demands and needs of social development and historical progress. A whole new generation of intellectuals began to form in the country, having passed the nation’s pains and sufferings, all the pitiful, terrible, tragic fate with their hearts and bodies, and mobilized their entire being, intelligence, mind, and life for freedom, freedom, and development.